Konsepsi "Limited Guarantee Terhadap Nasabah Bank Dalam Undang-undang No.24 Tahun 2004 Tentang Lembaga Penjamin Simpanan - Ginting, Jamin (LAW REVIEW, 2006)
The condition that unable to pay the fund to the customer at the hank that has a liquidation experience is a bad image for the financial condition in Indonesia, to evade this awful image the government has tried to ensure all customers fund through Keppres No.26 Tahun 1998 Tentang Jaminan Kewajiban Pembayaran Bank Umum that has been renewed by Keputusan Presiden Rl No. 17 Tahun 2004 and Moil between Bank Indonesia and Republic Indonesia Finance Ministry at 8 April 2004, along with KMK No.l89/KMK.06/2004 about the government will ensure all customers fund in bank that will be liquidated, which this condition is known as Blanked Guarantee. Actually this condition is very dangerous to the Indonesian government where government has to ensure all customers fund so through UU No.24 Tahun 2004, been established Lembaga Penjamin Simpanan which limit the guarantee to the customers fund in liquidated bank in certain amount and this is known as Limited Guarantee, the application of the Limited Guarantee is ruled in Undang-Undang No. 24 Tahun 2004 tentang Lembaga Penjamin Simpanan.